2016
DOI: 10.21003/ea.v160-20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of logistics infrastructure on the functioning and development of regional economy

Abstract: Abstract. In the article, key factors of development and main elements of logistics infrastructure are outlined, their impact on different areas of regional economy is evaluated. The authors conducted comparative study of different groups of factors and built an econometric model for some of them. The resulting regression made it possible to find important interdependencies for Kazakhstan, namely: increase of the demand for transport and logistics services by 1% leads to GRP increase by 7.013 billion tenge (US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…e academic research on the relationship between logistics industry and economic system has achieved fruitful results. e related research mainly focuses on the supply chain management [3][4][5][6], enterprise logistics performance [7][8][9][10], logistics infrastructure [11][12][13][14], green logistics [15][16][17][18][19], the interactive development of logistics industry, manufacturing industry and retail industry [20,21], and the evaluation index of logistics industry development [22,23]. However, spatial pattern study of logistics industry and economic interaction coupling coordination is less, and the influence factor of these is much rarer.…”
Section: Introductionmentioning
confidence: 99%
“…e academic research on the relationship between logistics industry and economic system has achieved fruitful results. e related research mainly focuses on the supply chain management [3][4][5][6], enterprise logistics performance [7][8][9][10], logistics infrastructure [11][12][13][14], green logistics [15][16][17][18][19], the interactive development of logistics industry, manufacturing industry and retail industry [20,21], and the evaluation index of logistics industry development [22,23]. However, spatial pattern study of logistics industry and economic interaction coupling coordination is less, and the influence factor of these is much rarer.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies by Kiel et al (2014), Purwanto et al (2017, Liu et al (2022) showed a positive impact of transport infrastructure development on competitiveness. Raimbekov et al (2016) studied the impact of logistics infrastructure on regional economic development, taking Kazakhstan as an example. And Lean et al (2014) tested the relationship between logistics development and economic growth in both the short and long term, taking China as an example, applying the Granger test.…”
mentioning
confidence: 99%